Europe’s Climate Target for 2050: An Assessment - Richard S. J. Tol (Intereconomics)
Abstract Decarbonisation is harder for transport, heating, industry and agriculture. That is, a doubling of the decarbonisation rate requires much more than a doubling of the policy effort. The low-hanging fruit has been picked.